THE RELATIONSHIP BETWEEN SELF-EFFICACY AND FUTURE ANXIETY AMONG MALE CORRECTIONAL INMATES APPROACHING RELEASE - Nathan, Tanella Amabel; Soetikno, Naomi (Journal of Social and Economics Research, 2024)
The inmates of correctional institutions are individuals who are serving a prison sentence for a specific period, life imprisonment, or death penalty while awaiting a decision and undergoing rehabilitation in correctional institutions. As they approach their release, inmates often experience concerns about receiving negative perceptions from society and/or being rejected by their environment. This anxiety regarding future changes can be referred to as future anxiety. Previous research has indicated that self-efficacy is one of the factors influencing future anxiety. Self-efficacy is the belief that individuals can manage a situation and achieve positive outcomes. This study employs a correlational quantitative approach involving 249 participants to examine the relationship between self-efficacy and future anxiety among male inmates approaching release. Data collection was conducted by distributing questionnaires utilizing the General Self-Efficacy Scale (α = 0.889) and Future Anxiety Scale (α = 0.926). Data analysis revealed a correlation coefficient of r(249) = -0.2, p = 0.002<0.01, indicating a significant negative relationship between self-efficacy and future anxiety among male inmates approaching release. Future research is suggested to explore the extent of self-efficacy’s role in influencing future anxiety among inmates. Understanding this relationship could establish the effectiveness of self-efficacy as a strategy to reduce future anxiety.